A Skills beyond School Review of Denmark - Field, Simon (OECD Publishing, 2012)
Higher level vocational education and training (VET) programmes are facing rapid change and intensifying challenges. What type of training is needed to meet the needs of  changing economies? How should the programmes be funded?  How should they be linked to academic and university programmes?  How can employers and unions be engaged?   This country report on Denmark looks at these and other questions, and is part of the Skills beyond School series, OECD policy reviews of postsecondary vocational education and training.
Keywords: Education; Denmark